Model of the antecedent and consequences of digital inclusion: a study among entreprenuership / Faradillah Iqmar Omar, Nur Ajeerah Othman and Nor Hafizah Abdullah - Omar, Faradillah Iqmar; Othman, Nur Ajeerah; Abdullah, Nor Hafizah (Faculty of Communication & Media Studies, 2020)
The study aims to develop a model of digital inclusion among entrepreneurs (SMEs) in Malaysia. The existing digital gap instrument is geared towards access, skills and motivational aspects of using ICT and looking at the issue of usage gaps, whereas digital inclusion is about how users benefit from the use of ICT as well as prevent the occurrence of digital imperfections. Digital inclusion is a holistic approach that a) measures the impact of ICT on economic and social (new skills), b) an environment that can help the economic and society capabilities benefit from ICT (innovation and entrepreneurship), c) Clear policy and identify opportunities for public-private collaboration (robust legislation and law). Hence, the formation of antecedent and digital inclusion model is a new lead in measuring individual and community development. The objective of the study is to determine the re-concept of digital inclusion and to test the identified digital domain domains such as communication networks, entertainment, and search for business information, e-commerce, creating business sites, advertising and product marketing. Subsequently, the expected outcome of the study is to introduce a new digital inclusiveness instrument among entrepreneurs (SMEs) in Malaysia based on a number of domains that have been tested and identified.